Skrining Aktivitas Antibakteri dan Antijamur dari Isolat Bakteri Marinobacter Hydrocarbonoclasticus NAR7 - I Gusti Gde Agung Anantawikrama; Anak Agung Gede Indraningrat; Ni Wayan Widhidewi (Aesculapius Medical Journal, 2024)
Infectious diseases caused by bacteria and fungi are global health issues, including in Indonesia. Previous studies reported one bacterial isolate associated with the seaweed Caulerpa lentillifera, namely Marinobacter hydrocarbonoclasticus NAR7, which showed antibacterial activity against Streptococcus mutans based on the perpendicular streak method. This study is alaboratory research with a descriptive method. Isolate M. hydrocarbonoclasticus NAR7 was grown in 100 mL of nutrient broth supplemented with artificial seawater for seven days. The obtained supernatant was separated from the cell mass by filtration, and the supernatant was extracted with ethyl acetate at a ratio of 1:1 (v/v) and further evaporated at 40°C to obtain a thick extract. The crude ethyl acetate extract obtained was tested against Gram-positive bacteria (Staphylococcus aureus ATCC 25923, Streptococcus mutans FNCC 0405), and Gram-negative bacteria (Escherichia coli ATCC 25922, and Klebsiella pneumoniae ATCC 700603) using the Kirby-Bauer method. Screening results showed that the extract was only active against Staphylococcus aureus ATCC 25923 with an average inhibitory zone diameter of 7.32±0.57 mm, which is classified as moderate antibacterial activity. Meanwhile, the extract did not form inhibitory zone diameters against other test bacteria. Antifungal screening showed that the extract could not inhibit the growth of Candida albicans and Aspergillus flavus fungi. These results overall indicate the initial potential of antibacterial activity from the M. hydrocarbonoclasticus NAR7 isolate. Further optimization efforts, including extraction with different solvents, are required.